Transition from MDG 2 to SDG 4: A Study of the Contributions of the „Right to Play‟ In Promoting Quality Education in Ghana - Amenorhu, F.Y. (University Of Ghana, 2018)
The „Right To Play‟ (RTP) is a non-state actor that uses play-based approach to educate students in some countries across the world with the aim of promoting inclusive and equitable quality education and ensuring peaceful and just societies. This dissertation studied the contributions that the play-based approach of RTP made to the attainment of MDG 2 in Ghana and the contributions that the play-based approach is likely to make towards the attainment of SDG 4 in Ghana. The study is hinged on the theory of Pluralism. Pluralism is chosen as the relevant theory for this study because of its ability to explain the capabilities of non-state actors, such as the RTP, which enable them to influence and contribute significantly to the educational development of several states including Ghana. The dissertation is a case study research and it adopts a qualitative approach, using both secondary and primary data. The researcher used semi-structured interview guides to collect the requisite primary data from the target population in Northern Ghana. The findings revealed that, the play-based approach contributed significantly to the attainment of the 1st and 3rd indicators of MDG 2, which respectively measured the enrolment rate in primary schools and the literacy rate of youth who fall within the age bracket of 15-24 years in Ghana. The findings of the study also show that the play-based approach is likely to make positive contributions towards the 1st, 2nd, 5th, 6th and 7th targets set for the attainment of SDG 4 in Ghana. Apart from SDG 4, the approach will also make significant contributions towards the attainment of SDGs 5, 10 and 16. In conclusion, the study indicates that, if the Ghanaian Ministry of Education and the Ghana Education Service integrate the play-based approach into the complete curriculum of basic schools (KG to primary 6) in Ghana, it will be possible for many children from typically difficult-to-reach groups (which include children from disadvantaged economic and ethnic groups; children with disabilities; and children of nomadic people) within the rural areas of the Northern Region and other rural areas in Ghana to have access to inclusive and equitable quality education.
MA
Keywords: Right to Play (RTP); Quality Education; Ghana